New Address Shift Linear Feedback Shift Register Generator - Moulood, Kholood J (Al-Nahrain Journal of Science, 2017)
In this paper we introduced a design of new pseudo random generator, which generate binary sequences that would be used as an encryption key in Stream Cipher Cryptosystem (SCC). The proposed generator consists of number of Linear Feedback Shift Registers (LFSR’s), which are considered the basic unit of SCC and some nonlinear functions. The proposed cryptosystem called. Address Shift LFSR (ASLFSR) cryptosystem. Lastly, ASLFSR generator subjects to set of Basic Efficient Criteria (BEC) to examine its output to prove its efficiency.